Kesantunan Berbahasa Guru Bahasa Indonesia dalam Proses Belajar Mengajar di SMA Negeri 2 Lintau Buo - Gusriani, Nuri; Atmazaki, Atmazaki; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was (1) to describe the type of speech act Indonesian teachers SMAN 2 Lintau Buo in teaching and learning, (2) describe the principle of linguistic politeness Indonesian teachers SMAN 2 Lintau Buo during the learning process takes place. The research data is used utterances Indonesian teachers in teaching and learning at SMAN 2 Lintau Buo. The data source of this study is three Indonesian teachers. Data collected by the techniques involved ably refer freely and technique note. The findings of the study as follows. First, there are five kinds of speech acts used by Indonesian teachers SMA Negeri 2 Lintau Buo, namely (1) directive, (2) representative, (3) the declaration, (4) commissive, (5) expressive. Secondly, the kind of politeness maxims used there are four, namely (1) wisdom, (2) generosity, (3) praise, and (4) compatibility.